Towards Experimental Handbooks in Catalysis - Trunschke, Annette; Bellini, Giulia; Boniface, Maxime; Carey, Spencer J.; Dong, Jinhu; Erdem, Ezgi; Foppa, Lucas; Frandsen, Wiebke; Geske, Michael; Ghiringhelli, Luca M.; Girgsdies, Frank; Hanna, Rania; et al. (Topics in Catalysis, 2020)
The “Seven Pillars” of oxidation catalysis proposed by Robert K. Grasselli represent an early example of phenomenological descriptors in the field of heterogeneous catalysis. Major advances in the theoretical description of catalytic reactions have been achieved in recent years and new catalysts are predicted today by using computational methods. To tackle the immense complexity of high-performance systems in reactions where selectivity is a major issue, analysis of scientific data by artificial intelligence and data science provides new opportunities for achieving improved understanding. Modern data analytics require data of highest quality and sufficient diversity. Existing data, however, frequently do not comply with these constraints. Therefore, new concepts of data generation and management are needed. Herein we present a basic approach in defining best practice procedures of measuring consistent data sets in heterogeneous catalysis using “handbooks”. Selective oxidation of short-chain alkanes over mixed metal oxide catalysts was selected as an example.
CRIS-Team Scopus Importer:2023-09-25
Keywords: Artificial intelligence; Best practice; Data science; Descriptor; Machine learning; Rigorous protocols; Standard operation procedure